STUDY OF SUPERCONDUCTING BY MICRO-RAMAN SPECTROSCOPY - González, J. C. (2005)
YBa2Cu3(O)7-x thin film sample was studied by micro-Raman spectroscopy. The investigation involved aspects like crystal orientation, uniformity, secondary phases, impurities, oxygen content and defects, based on the speciftc Raman selection rules for YBa2Cu3(O)7-x and polarized Raman scattering experiments.